Analisis Yuridis Mallpraktek Perawat Menurut Undang-Undang Nomor 38 Tahun 2014 Tentang Keperawatan - Rachmawati, Junia; Hamzah, Any Suryani (Private Law, 2024)
This research aims to find out nurses' responsibilities if they make mistakes while on duty and do not fulfill their obligations according to the provisions of Law Number 38 of 2014 concerning Nursing. Furthermore, it analyzes dispute resolution concerning malpractice by nurses under the provisions of Law Number 38 of 2014 2014 on Nursing. The type of research is normative legal research. The research conclusion is that the nurse's civil liability for malpractice against patients is subject to the work agreement that has been made and mutually agreed between the nurse and the hospital and with absolute liability (strict liability), which refers to the provisions of Article 1601 jo. 1601a Civil Code. If it is expressly agreed in the work agreement that the nurse is fully responsible for malpractice, then the nurse bears all losses caused by his actions, based on the provisions of Article 1365 jo. Article 1366 of the Civil Code, and Article 310 of Law Number 17 of 2023 concerning Health. Forms of dispute resolution if malpractice occurs include compensation costs which will be paid to the patient (in this case the victim). Patients who experience losses due to malpractice actions by nurses can take legal action through litigation and non-litigation channels. The litigation is by filing a lawsuit before the District Court following the relative competence of the court. The non-litigation is in the form of mediation, namely peaceful resolution of disputes. This mediation process is divided into two, namely those carried before the court and outside the court.